Software Lets a Cell Phone Work Like a Mouse. (Computer (00189162), 2008)
The article describes computer interface software which would allow for a cellular phone or other mobile device to function as a mouse. Details are are given outlining the software approach of mapping image processing to pinpoint screen interfacing. Comments are also given regarding its potential applications and refinements still to be implemented.